Median Arcuate Ligament Syndrome With Celiac Artery Aneurysm and Dissection. (August 2020) - Michell, Hans; Nezami, Nariman; Dewald, Aaron; Bhave, Anant; Morris, Christopher; Akselrod, Dmitriy
Median arcuate ligament syndrome (MALS) is the chronic symptomatic compression of the celiac artery by the median arcuate ligament. A known potential sequela of MALS is celiac artery aneurysm, which could predispose the diseased artery to dissection. However, the presence of celiac artery dissection and MALS is yet to be reported. Here, we present a case of MALS with a coincident celiac artery aneurysm and dissection.